Leadership Values in the Sapta Sila Text of Pencak Silat Pagar Nusa (PSNU) Padepokan Jabalahad - Ahmad Rosyid; Khoirotul Izzah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
Sapta Sila text is a gist of serat Sastra Gendhing wich contains the concept of leadership from the famous figure namely Sultan Agung Hanyakrakusuma who is the third king of Mataram Islam Kingdom. This serat in Pagar Nusa Padepokan Jabalahad was introduced by the caregiver of Padepokan Jabalahad, Gus Iman Widodo. This researh are expected to provide an introduction that the values and philophy of Javanese still relevant to be used as a guide of life especially for Javanese people. One of Javanese leader who need to be imitated is Sultan Agung Hanyakrakusuma by knowing his principle of leadership wich is used as a refference for the formation of Sapta Sila. This Sapta Sila was pledged by Pagar Nusa Padepokan Jabalahad when they were appointmen to be a new members or to be a senior. This research uses a literature study method were the research makes library documents as a primary sources by using discriptive approach to provide an overview of an event in a cotext. This study uses a book entitled “Serat Sastra Ghending : Warisan Spiritual Sultan Agung yang Berguna untuk Memandu Olah Pikir dan Olah Dzikir” by Partini (2008) and a research by Ghulam Abdurrahman entitled “Nilai – Nilai Pendidikan Akhlak dalam Teks Sapta Sila Pencak Silat Nahdlatul Ulama (PSNU) Pagar Nusa” as a primary source. Based on this study, shows that there are seven leadership concepts in Sapta Sila Pencak Silat Pagar Nusa Padepokan Jabalahad namely : Swadana Maharjeng Tursita, Bahni Bahna Amurbeng Jurit, Rukti Setya Garba Rukmi, Sripandanyasih Krami, Galugana Hasta, Stiranggana Cita, Smara Bhuni Adi Manggala. This concept demand that Pagar Nusa Padepokan Jabalahad not only active in the world of pencak silat but to be able to keep a vows in the Sapta Sila and practice it in their daily lives. There are seven values of a leadership contained in Sapta Sila, including the religious value that embodied in the Sapta Sila number four; Visionary on the third and sixth precepts, morals on the first and second precepts; Teladan in second and seventh precpets; wisdom on the second; fifth and sixth precepts; integrity in the first and seventh precepts; and Reponsibility in the first and second precepts.